2002
DOI: 10.1038/sj.onc.1205104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of viral-cellular fusion transcripts in a large series of HPV16 and 18 positive anogenital lesions

Abstract: Persistent high risk type human papillomavirus (HR ± HPVs) infections induce dysplasia or cancer of the anogenital tract, most notably of the uterine cervix. The viral genome usually persists and replicates as an episomal molecule in early dysplasia, whereas in advanced dysplasia or cervical cancer HPV genomes are frequently integrated into the chromosomal DNA of the host cell. Previous studies suggested that modi®cation of critical cellular sequences by integration of HPV genomes might signi®cantly contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
129
3
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 43 publications
11
129
3
7
Order By: Relevance
“…HPV18 is frequently associated with adenocarcinoma (Lombard et al, 1998) and preferentially integrates at the MYC locus (Ferber et al, 2003b). However, we and others (Brink et al, 2002;Wentzensen et al, 2002) have also found HPV16 DNA at this locus. It is well established that cervical neoplasia start at the squamous columnar junction of the cervix epithelium, a part of the mucosa in which the basal cells, exposed to infections, have the potential to differentiate into either squamous or glandular cells.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…HPV18 is frequently associated with adenocarcinoma (Lombard et al, 1998) and preferentially integrates at the MYC locus (Ferber et al, 2003b). However, we and others (Brink et al, 2002;Wentzensen et al, 2002) have also found HPV16 DNA at this locus. It is well established that cervical neoplasia start at the squamous columnar junction of the cervix epithelium, a part of the mucosa in which the basal cells, exposed to infections, have the potential to differentiate into either squamous or glandular cells.…”
Section: Discussionmentioning
confidence: 45%
“…Up to 181 different sites corresponding to 243 cases have been observed (Brink et al, 2002;Klimov et al, 2002;Wentzensen et al, 2004;Kraus et al, 2005;and our unpublished results). In spite of this scattering, it is remarkable that the chromosome band 8q24, to which MYC maps, is the most recurrent site for insertion of HPV DNA, as it is found in 10.7% (26/243) of the all cases (Du¨rst et al, 1987;Popescu et al, 1987;Couturier et al, 1991;Hori et al, 1991;Brink et al, 2002;Wentzensen et al, 2002;Ferber et al, 2003b;Ziegert et al, 2003;Kraus et al, 2005). A low level of MYC overexpression has been found in HeLa cells harboring HPV18 sequences in chromosome band 8q24 (Du¨rst et al, 1987;Lazo et al, 1989), but no evidence of MYC activation directly related to HPV insertion at the MYC locus has been published.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations